Conversation Circles to Foster Interactions (2021)
ABSTRACT: This action research study whose participants were ninth-graders of a public institution was aimed at exploring the usefulness of conversation circles to foster different types of interactions. Data were collected through a research journal, two interviews with the cooperating teacher at two different moments, a focus group, a questionnaire, and video recordings of four conversation circles. Data analysis showed that conversation circles are effective to foster interactions and provide a space to use the target language and construct knowledge. It also showed that the teacher’s role is important as a facilitator and promoter of interaction in this process. There were also limitations related to time constraints that could have kept me from achieving better results.